(3HQfGeL EdcJQhfji bGFe Ydi GdeONd GdJhGUdi dJfejI egGQGJ GdJMOK h GdcJGHI dOGQSi GddZI GdYQHjI GdfGWbjf HZjQgG ai GdeSJhi GdeJhSW (B/ s - (3gfGA ESeGYjd eJhdi eMeOs; (3CSGeI eMehO aQGL (B: s; (3EjeGf CMeO gQjOi (B: s; (3Sdhi aJMi eMehO GdeUQi (B: s ((3GdbGgQI (B: s (3gfGA ESeGYjd eJhdi eMeO (B: s, 2021)
(3gOa GdHMK Edi JYQa aGYdjI GdHQfGeL GdEdcJQhfi GdbGFe Ydi GdeONd GdJhGUdi ai JfejI egGQnJi GdJMOK h GdcJGHI dOGQSi GddZI GdYQHjI ef GdfGWbjf HZjQgG ai GdeSJhi GdeJhSW(B: (3h dJMbjb gPG GdgOa bGeJ GdHGMKI HEYOGO bGFeI egGQGJ GdJMOK(B: (3h bGFeI egGQGJ GdcJGHI HeG jfGSH OGQSi GddZI GdYQHjI ef GdfGWbjf HZjQgG(B: (3h JUeje GdHQfGeL GdEdcJQhfi GdebJQM dJfejI egGQGJ GdJMOK h GdcJGHI dOGQSi GddZI GdYQHjI ef GdfGWbjf HZjQgG(B: (3h HWGbI edGMXI dbjGS egGQGJ GdJMOK h HfGA GNJHGQ dbjGS egGQGJ GdcJGHI(B: (3h HYO GNJjGQ eLehYI GdHMK Je JWHjb HWGbI edGMXI dbjGS egGQGJ GdJMOK(B: (3h GNJHGQ dbjGS egGQGJ GdcJGHI JWHjkbG bHdjG(B: (3Ke Je JOQjS GdHQfGeL(B: (3h HYO GdGfJgGA ef JWHjb GdHQfGeL(B: (3Je JWHjb GdHWGbI h GdGNJHGQ JWHjbG HYOjGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe GdJYdje GdYGdi h GdJYdje GdeSJeQs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdeONd GdJhGUdis; (3HQfGeL GdcJQhfis; (3egGQGJ GdJMOK h GdcJGHIs